Agricultural Waste. (1st October 2013) - Zhang, Zhenyuan; Li, Chaona; Davies, Evan G. R.; Liu, Yang
Abstract : The negative environmental impacts of agricultural waste typically draw attention. However, agricultural waste has beneficial uses as an energy source, chemical recycling agent, and chemical adsorbent. This review examines the characterization, reuse, treatment, and management (minimization) of agricultural waste.